2023
DOI: 10.3390/ani13132052
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Data Analysis from Ovine and Bovine RNA-Seq Identifies Pathways and Key Genes Related to Cervical Dilatation

Abstract: The present study developed a review and exploration of data in public and already validated repositories. The main objective was to identify the pathways involved in ruminants’ cervical dilatation, which are conserved between cattle and sheep in the follicular and luteal phases of the reproductive cycle. In cattle, 1961 genes were more differentially expressed in the follicular phase and 1560 in the luteal phase. An amount of 24 genes were considered exclusively expressed from these. A total of 18 genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Shimizu et al [ 35 ] demonstrated that AGT was part of a gene cluster downregulated by E2 and upregulated by P4, in accordance with elevated expression at Day 7 in this study. An analysis of data from the cervices of the same animals also showed differences in AGT expression, which was elevated in the luteal phase relative to the follicular phase [ 42 ]. In human endometrial stromal cells, decidualization was associated with an increase in expression of prorenin and other components of the renin-angiotensin system [ 76 ], suggesting that AGT upregulation is essential to facilitate decidualization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimizu et al [ 35 ] demonstrated that AGT was part of a gene cluster downregulated by E2 and upregulated by P4, in accordance with elevated expression at Day 7 in this study. An analysis of data from the cervices of the same animals also showed differences in AGT expression, which was elevated in the luteal phase relative to the follicular phase [ 42 ]. In human endometrial stromal cells, decidualization was associated with an increase in expression of prorenin and other components of the renin-angiotensin system [ 76 ], suggesting that AGT upregulation is essential to facilitate decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…The current study uses endometrial tissues harvested in tandem with endocervical tissues derived from oestrus-synchronized heifers. The data on the cervical transcriptome of these animals have been published previously by our group [ 40 , 41 ] and also later analysis of this dataset was performed by Gonçalves et al [ 42 ], who compared the differentially expressed genes (DEGs) for the follicular and luteal phases. In this study, RNA-sequencing (RNA-seq) data was generated from samples derived from the endometrial tissue of oestrus-synchronized heifers during the perioestrus period, allowing investigation of changes in the transcriptome as the endometrium was exposed to changes in E2 and elevation in P4 concentrations, with the final sample taken at Day 7 after the onset of oestrus (early luteal phase).…”
Section: Introductionmentioning
confidence: 99%